2012
DOI: 10.5194/acp-12-5787-2012
|View full text |Cite
|
Sign up to set email alerts
|

Halogenation processes of secondary organic aerosol and implications on halogen release mechanisms

Abstract: Abstract. Reactive halogen species (RHS), such as X·, X 2 and HOX containing X = chlorine and/or bromine, are released by various sources like photo-activated sea-salt aerosol or from salt pans, and salt lakes. Despite many studies of RHS reactions, the potential of RHS reacting with secondary organic aerosol (SOA) and organic aerosol derived from biomass-burning (BBOA) has been neglected. Such reactions can constitute sources of gaseous organohalogen compounds or halogenated organic matter in the tropospheric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 84 publications
2
30
0
Order By: Relevance
“…The rate constant of the isoprene-chlorine reaction at 25 • C (2.64-5.50 × 10 −10 molecules −1 cm 3 ; Fantechi et al, 1998;Orlando et al, 2003;Ragains and Finlayson-Pitts, 1997) is much larger than the rate constant of the isoprene-OH reaction (1.00 × 10 −10 molecules −1 cm 3 ; Atkinson and Arey, 2003), suggesting that isoprene-chlorine chemistry could compete with isoprene-OH chemistry under certain conditions. Moreover, reactions between chlorine and isoprene or isoprene-derived SOA could serve as a reactive chlorine sink in the atmosphere, as has been proposed for reactions between chlorine and biogenic SOA (Ofner et al, 2012). To our knowledge, SOA formation from chlorine-initiated oxidation of isoprene has not been reported in the literature.…”
Section: S Wang and L Hildebrandt Ruiz: Secondary Organic Aerosomentioning
confidence: 75%
See 2 more Smart Citations
“…The rate constant of the isoprene-chlorine reaction at 25 • C (2.64-5.50 × 10 −10 molecules −1 cm 3 ; Fantechi et al, 1998;Orlando et al, 2003;Ragains and Finlayson-Pitts, 1997) is much larger than the rate constant of the isoprene-OH reaction (1.00 × 10 −10 molecules −1 cm 3 ; Atkinson and Arey, 2003), suggesting that isoprene-chlorine chemistry could compete with isoprene-OH chemistry under certain conditions. Moreover, reactions between chlorine and isoprene or isoprene-derived SOA could serve as a reactive chlorine sink in the atmosphere, as has been proposed for reactions between chlorine and biogenic SOA (Ofner et al, 2012). To our knowledge, SOA formation from chlorine-initiated oxidation of isoprene has not been reported in the literature.…”
Section: S Wang and L Hildebrandt Ruiz: Secondary Organic Aerosomentioning
confidence: 75%
“…3. The oxidizing capacity of chlorine radicals has also been demonstrated for select biogenic SOA derived from α-pinene, catechol, and guaiacol, where halogenation led to significant SOA aging, formation of high-molecular-weight compounds, and particle growth (Ofner et al, 2012). High reactivity of chlorine radicals towards isoprene and its reaction products meant that extensive SOA processing could be easily achieved within laboratory timescales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of halogens in the aging process of organic aerosols was determined by Ofner and coworkers (2012) using long-path FTIR spectroscopy (LP-FTIR), attenuated-total reflection FTIR (ATR-FTIR), UV/VIS spectroscopy, and ultrahigh resolution mass spectroscopy (ICR-FT/MS). They concluded that the aerosol-halogen interaction might strongly contribute to the influence of organic aerosols on the climate system (Ofner et al, 2012).…”
Section: Advanced Aspects Of Spectroscopy 64mentioning
confidence: 99%
“…The role of halogens in the aging process of organic aerosols was determined by Ofner and coworkers (2012) using long-path FTIR spectroscopy (LP-FTIR), attenuated-total reflection FTIR (ATR-FTIR), UV/VIS spectroscopy, and ultrahigh resolution mass spectroscopy (ICR-FT/MS). They concluded that the aerosol-halogen interaction might strongly contribute to the influence of organic aerosols on the climate system (Ofner et al, 2012). Khalizov and coworkers (2010) investigated the heterogeneous reaction of nitrogen dioxide (NO2) on fresh and coated soot surfaces to assess its role in night-time formation of nitrous acid (HONO) in the atmosphere using ATR-FTIR (Khalizov et al, 2010).…”
Section: Attenuated Total Reflection -Fourier Transform Infrared (Atrmentioning
confidence: 99%